Resilience as pathway diversity: linking systems, individual, and temporal perspectives on resilience - Steven J. Lade (Resilience Alliance, 2020)
Approaches to understanding resilience from psychology and sociology emphasize individuals' agency but obscure systemic factors. Approaches to understanding resilience stemming from ecology emphasize system dynamics such as feedbacks but obscure individuals. Approaches from both psychology and ecology examine the actions or attractors available in the present, but neglect how actions taken now can affect the configuration of the social-ecological system in the future. Here, we propose an extension to resilience theory, which we label "pathway diversity", that links existing individual, systems, and temporal theories of resilience into a common framework. In our theory of pathway diversity, resilience is greater if more actions are currently available and can be maintained or enhanced into the future. Using a stylized model of an agricultural social-ecological system, we show how pathway diversity could deliver a context-sensitive method of assessing resilience and guiding planning. Using a stylized state-and-transition model of a poverty trap, we show how pathway diversity is generally consistent with existing definitions of resilience and can illuminate long-standing questions about normative and descriptive resilience. Our results show that pathway diversity advances both theoretical understanding and practical tools for building resilience.